Comparison of the quantitative performance of a Q‐Exactive high‐resolution mass spectrometer with that of a triple quadrupole tandem mass spectrometer for the analysis of illicit drugs in wastewater. (27th June 2013) - Fedorova, Ganna; Randak, Tomas; Lindberg, Richard H.; Grabic, Roman
Abstract : RATIONALE: Analysis of drugs in wastewater is gaining more interest, as new approaches to estimate drug consumption from the amount of drug residues in wastewater have been proposed. The aim of this study was to compare the quantitative performance of high‐resolution mass spectrometry with that of triple quadrupole mass spectrometry. METHODS: A Q‐Exactive mass spectrometer was operated in full scan (HRFS) (70 000 FWHM) and product scan (HRPS) (17 500 FWHM) modes. The first and third quadrupoles of the QqQ MS/MS instrument were operated at 0.7 FWHM. A mass‐extracted window of 5 ppm around the theoretical m/z of each analyte was used to construct chromatograms. An HESI‐II ion source was used for the ionization of target compounds. In‐line‐SPE‐LC configuration was used for the extraction and separation of target analytes. RESULTS: All three methods showed good linearity and repeatability. High‐resolution detection of product ions exhibited better sensitivity and selectivity for some compounds. For most of the tested compounds, LOQs ranged from 0.46 to 20 ng L –1 . Good agreement between measured and nominal concentrations was observed for most of the compounds at different levels of fortification. Both MS/MS methods showed good selectivity, while HRFS gave some false positive results. CONCLUSIONS: The Q‐Exactive mass spectrometer proved to be suitable for trace detection and quantification of most of the tested drugs in wastewater, with performance comparable to that of the commonly used MS/MS triple quadrupole, but with better selectivity. Copyright © 2013 John Wiley & Sons, Ltd.